Algorithms of networked control system design - Olejnichenko, Kateryna (Видавництво Львівської політехніки, 2010)
This paper discusses design of Networked Control Systems (NCS). NCS are distributed control systems whose sensors, actuators and controllers are interconnected by shared industrial network. The major NCS problem is network-induced delays. These delays caused by the sharing of communication medium can be constant, bounded, or even random and can degrade system's performance. The main goal of the paper is to present the methodology of NCS design and the behaviour algorithms for individual NCS nodes. Finally, the control methods suitable for NCS are shortly presented.
Keywords: control system; control design; delay compensation; algorithms; communication networks